Signaling specificity by frizzled receptors in Drosophila. - Boutros, M.; Mihaly, J.; Bouwmeester, T.; Mlodzik, M. (Science, 2000)
Wnt-Frizzled (Fz) signaling pathways play recurring important roles during the development and homeostasis of vertebrates and invertebrates. Fz receptors can signal through beta-catenin-dependent and -independent pathways. In Drosophila, Fz and Fz2 are redundant receptors for Wg. In addition, Fz conveys signals through a distinct pathway to organize planar polarization of epithelial structures. We demonstrate that the cytoplasmic sequences of Fz2 and Fz preferentially activate the beta-catenin and planar polarity cascade, respectively. Both receptors activate either pathway, but with different efficiencies. Intrinsic differences in signaling efficiency in closely related receptors might be a general mechanism for generating signaling specificity in vivo.